Parameter extraction of coupling-of-modes equations including coupling between two surface acoustic waves on SiO2/Cu/LiNbO3 structures. (6th June 2018) - Huang, Yulin; Bao, Jingfu; Li, Xinyi; Zhang, Benfeng; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: This paper describes extraction of parameters of an extended coupling-of-modes (COM) model including coupling between Rayleigh and shear-horizontal (SH) surface acoustic waves (SAW) on the SiO2 -overlay/Cu-grating/LiNbO3 -substrate structure. First, dispersion characteristics of two SAWs are calculated by the finite element method (FEM), and are fitted with those given by the extended COM. Then variation of COM parameters is expressed in polynomials in terms of the SiO2 and Cu thicknesses and the rotation angle Θ of LiNbO3 . Then it is shown how the optimal Θ giving the SH SAW suppression changes with the thicknesses. The result agrees well with that obtained directly by FEM. It is also shown the optimal Θ changes abruptly at certain Cu thickness, and is due to decoupling between two SAW modes.